Technological characterization of indigenous lactic acid bacteria from Moroccan camel milk for their potential use as starter or adjunct culture - Moussaid, Siham; Bouhlal, Outmane; Benali, Aouatif; Kabbour, Mohammed Rachid; Ounine, Khadija; El Maadoudi, El Haj (Folia microbiologica, 2021)
This study aimed to isolate lactic acid bacteria (LABs) of technological interest from Moroccan camel milk and select starter or adjunct culture for dairy product manufacturing. The phenotypic and biochemical identification of 47 isolates revealed the existence of ten Lactococcus lactis, eleven Lactobacillus plantarum, three Lactobacillus brevis, two Lactobacillus paracasei, eleven Enterococcus spp., seven Lactococcus spp. and two Lactobacillus spp. Our strains showed a fast acidifying ability (ΔpH ranged between 0.69 ± 0.01 and 1.22 ± 0.05 after 6 h), high proteolytic and autolytic activities (1.93 ± 0.02 to 9.9 ± 0.022 mM glycine and 15.21 ± 2.21% to 83.24 ± 1% respectively), and an important lipolytic and free radical scavenging capacity. Furthermore, they were able to use citrate, to produce exopolysaccharide, and they exhibited antibacterial activity against Gram-negative and Gram-positive pathogenic bacteria and had no hemolytic activity. This study has shown that Moroccan camel milk represents a rich biotope of interesting LABs for dairy products industry.
Keywords: Animals; Food Microbiology; Lactobacillales; potravinářská mikrobiologie; zvířata; mléko; Camelus; mléčné výrobky; Dairy Products; velbloudi; Milk